Personagens em busca de identidade em Jaime Bunda e a morte do americano, de Pepetela - Anjos, Fernando Serafim dos (Universidade Federal de São Carlos, 2020)
This study has, as main intention, the analysis of the novel Jaime Bunda and the death of the American (2003), by the Angolan writer Pepetela. Through the study of the characters of the novel – considering the way the relationships of the characters are built with each other, with the surrounding space and with themselves – I will try to highlight the identity search present in the narrative, using the approach of theoretical concepts such as parody, irony and literary carnivalization. The search for an identity is a recurrent factor in the literature, an ideia that becomes more evident in countries marked by the process of colonization. In this sense, Angola has a latent relation with the effects left by the presence of Portuguese conquerors, since it has a colonial history and anticolonial struggle still very recent. It is well known that Portuguese-language African literatures have been marked by identity issues in contemporary times and, therefore, it is necessary to observe these questions, pondering the effects of European colonization on the African continent. In Jaime Bunda and the death of the American, Pepetela, through the protagonist of the novel, explains this identity search in the relationship with other Angolan characters and with the foreigners present in the plot, as well as with the city of Benguela and, similarly, with the own country, culminating, finally, with itself. In this way, it is possible to establish some analyzes that emphasize the idea that there is a constant search about identity that can bring light to the issue about being Angolan in post-coloniality. In order to substantiate the analyzes of this work, we will also observe the way how the author constructs the novel by the bias of irony and also from the literary carnavalization, considering the parodic feature of this novel.
Characters looking for identity in Jaime Bunda and the death of the american, by Pepetela
Keywords: Identidade; Ironia; Carnavalização; Ficção angolana contemporânea; Pepetela; Identity; Irony; Carnavalization; Contemporary angolan fiction; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS